Diversifikasi produk dan optimalisasi digital marketing sebagai inovasi dan agripreneurship Kelompok Wanita Tani Aglonema Desa Rabak - Arofah, Anastasia Anggarkusuma; Fitriana, Aning; Putranto, Afif Hendri; Aprianti, Aprianti; Syahputra, Alridho Okta (Penamas: Journal of Community Service, 2025)
The Aglonema Women Farmers Group is a women's empowerment group in the agricultural sector located in Rabak Village, Purbalingga Regency. This community service aims to improve the understanding and skills of the members of the Aglonema Women Farmers Group in Rabak Village in the fields of product diversification and digital marketing. The method used is structured training through lectures, discussions, and direct practice. The stages of the community service activity implementation are: preparation, implementation, technology application, and evaluation. The training participants consisted of 30 members of the Women Farmers Group and PPL Rabak Village. The results of the activity showed increases in the pretest and post-test regarding participants' understanding and skills in product diversification (76.00%), digital marketing (72.80%), and financial recording (69.60%). This service contributes to the digital transformation of local MSMEs and to their increased competitiveness in the digital economy era. Follow-up service activities relate to agricultural aspects of technology utilisation.